Etymological and Semantic Aspects of the Concept of Homeland in English - K., Mardiyev T. (International Journal on Orange Technologies, 2023)
The article discusses the concept of patriotism and love for one's homeland as a fundamental Islamic value. The author emphasizes that the love for the homeland is a pure and original Islamic value that is elevated to the rank of worship. The article also highlights the importance of preserving peace and stability in society, which is essential for the realization of any noble plan, dream, and goal. The author explains that a patriot is a person who ardently and passionately desires what is in his/her homeland and considers oneself as one with the homeland. The article concludes that the concepts of the homeland, nationality, and religion are dear and sacred to humans, and one must take all possible measures to preserve the stability and tranquility of one's country.